Issues in the development of tropical Africa - Aboyade, Ojetunji (Ibadan, Nigeria : Ibadan University Press, 1976)
Issues in the development of tropical Africa examines economic development in continent in relation to the rest of the developed world. The book is covers topics that include: Africa in the world economy; Characteristics and development performance; influence of development theorizing; lesson from comparative experience; formulating policies and programmes and perspectives for social debate.
Includes bibliographical references and index.
lje 01/08/2018
Loans
Keywords: Economic policy; Economic development; Economic history; Africa, Sub-Saharan